Meningkatan Sarana Usaha Pengelolaan Sampah Plastik- Bank Sampah Sapujagad Kabupaten Magetan - astirin, okid parama; Hadi, Syamsul; Suryanto, Suryanto; Amanto, Bambang Sigit; Nugraha, Setya (Journal of Dedicators Community, 2024)
Waste both organic waste and inorganic waste is one of the threats and serious problems being faced in urban areas in Magetan. Milang Asri landfill (TPA) Magetan has experienced overload capacity conditions. The active role of the community in the form of Waste Bank and KSM (Community Self Help Group) in managing 3 R waste (Temporary waste disposal site) is needed to reduce the volume of waste piled up in Milangasri landfill. One alternative to solving the waste problem is to join the program of the Magetan "Sapu Jagad" Waste Bank, which was established in 2015. According to the Regulation of the Minister of Environment of the Republic of Indonesia Number 13 of 2012, a waste bank is a place for sorting and collecting waste that can be recycled and or reused to have economic value. The waste collected has been realized by the Sapu Jagad waste bank manager into various products of economic value: including bags, wallets, tables and chairs, crafts etc. Sapu Jagad Waste Bank also organizes education and training to convert waste into various products of economic value. Another activity is to campaign about the importance of the 3R principle (reuse, reduce, and recycle) both to the general public and to schools. Sapu Jagad Waste Bank plays an active role in waste processing, especially non-organic waste. The processed waste products from the Sapu Jagad waste bank have begun to be marketed online. The output of the activities that have been produced is that the waste bank has carried out the process of recording waste managed by the waste bank, waste bank funds and operational bookkeeping has been carried out using a simple program on the computer provided by the implementing team. The recording of sales of waste products into handicrafts and chairs and tables has improved. Production Process Aspects: The process of storing plastic water packaging and plastic packaging waste has been pressed using a plastic press machine that was also invested in the waste bank. The storage of plastic waste has become very space-efficient. Business Management Aspects: All aspects of business management, waste bank financial records, waste craft business records, canteen business, and waste bank training are still done manually. The expected output of the activity is a wider raw material storage and marketing process supported by adequate raw materials will be achieved. Mandatory output in the form of publication of the Journal of Community Service, mass media news published in online dailies and videos of activities uploaded on Youtube